Beyond the browser Web 2.0 and librarianship - Bridges, Karl 1964- (Santa Barbara, California Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2012)
"Authored by an experienced librarian, digital resource manager, and professor in the field of library science, this book explores the wide-reaching impact of second-generation web technologies on library organization and services--and how library staff must respond"--Provided by publisher.
Includes bibliographical references (pages 81-85) and index.
Keywords: Libraries and the Internet; Librarians -- Effect of technological innovations on; Web 2.0.